Data Storage Based Heart and Body Temperature Measurement Device - Nur Hudha Wijaya; Andi Gofer Alvian; Afif Zuhri Arfianto; Joessianto Eko Poetro; Farhad Waseel (Universitas Muhammadiyah Yogyakarta, 2020)
Body health is the most important thing for human life. The heart is one of the organs of the body that is very important for humans. The heart functions to regulate the circulation of oxygen-rich blood and to carry leftover food in the body. Heart rate illustrates how hard the heart works. The heart rate needs to be monitored to find out the patient's condition. BPM measurement and temperature is an activity of measuring heart rate and body temperature. The patient’s body temperature affects the patient's rapid heart to pump blood throughout the body. The study aims to design a heart rate and body temperature measuring device using an infrared LED as a transmitter and a photodiode as a receiver, an LM35 as the temperature sensor, and an LCD to display the final output. This tool uses an ATMega8 microcontroller as the controlling system. The device was completed with data storage and temperature indicators. The result of the test on the device showed that the device performed very well in measuring the heart rate and body temperature of adult patients aged 20 until 40 years old.